International business - Czinkota, Michael R., 1951-; Ronkainen, Ilkka A.; Gupta, Suraksha (New York, NY ; Cambridge : Cambridge University Press, 2021)
"We are grateful for the leadership position you, our market, have awarded to this book. Best-selling status in the international business field imposes an obligation to deliver cutting-edge innovations and improvements in terms of content as well as presentation. We honor your trust by doing our best to delight you through our presentation of conceptually sound, reality-based knowledge and by simplifying your task as students and teachers of international business. In this spirit of innovation, we offer you yet more value through International Business, 9th Edition"--
Revised edition of International business, c2011.
Includes bibliographical references and index.
Keywords: BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / International / General; International trade; International finance; Investments, Foreign; International business enterprises; International business enterprises -- Management